Analisis Pelayanan Hotel Terhadap Kepuasan Tamu : Studi Kasus Pada Hotel Pangrango I - Zuhdi, Saefudin (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2004)
To find out correlation between hotel services and consumersâ satisfation degree, the author used regression analysis, correlation coefficient, and determinant coefficient. From hypothesis result, ho was rejected and has was accepted because t stat.>t table. It means between hotel service (variable of x) and consumersâ satisfaction degree (variable of y) influence each other. To be found out regrresion result as y=24,46 + 0,60X. It mans if rate of x increases, rate of y increases 0,60 times. Correlation coefficient 0,598 show that variable of x and variable of y are significant and having positive correlation (getting close to r = +1). This fact has proven that services raising will afford satisfation to consumers. To be gotten determination coefficient rate 35,76 %; it means that hotel services contributes 35,76 % to consumersâ satisfaction degree, whereas the rest of 64,24% could be other factorsâ contribution. KeyWords : Management Strategy;